2013
DOI: 10.17129/botsci.38
|View full text |Cite
|
Sign up to set email alerts
|

Magnolia perezfarrerae a new species and a key to Mexican species of Magnolia section Talauma subsection Talauma (Magnoliaceae)

Abstract: A new rainforest species of Magnolia , from the eastern Selva Zoque of Chiapas, Mexico, is described and illustrated. Magnolia perezfarrerae belongs to section Talauma , subsection Talauma . It differs from M . equatorialis in having shorter leaf blades that are elliptic rather than lanceolate, longer petioles, and much shorter apices of the carpels. Unlike any published Mexican species of subsection Talauma , this new species presents a circumcissile dehiscence with abaxial portions of carpels detaching in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
0
8
0
4
Order By: Relevance
“…La variación morfológica observada entre M. mexicana respecto al individuo de Zumpahuacán (seis caracteres) y el de Malinalco (siete caracteres), sugiere también una diferenciación a nivel específico, ya que la reclasificación a nuevas especies de algunas poblaciones de M. mexicana ha resultado de variaciones morfológicas similares; por ejemplo, la reclasificación a M. perezfarrerae refirió variación en seis caracteres (Vázquez-García, Gómez-Domínguez, et al, 2013), la reclasificación a M. lacandonica consideró cuatro caracteres (Vázquez-García, Pérez-Farrera, et al, 2013), la reclasificación a M. zoquepopolucae contempló siete caracteres (Vázquez-García, De Castro-Arce, et al, 2012) y similar número de diferencias se consideraron en el resto de especies mexicanas de la sección Talauma recientemente descritas (Vázquez-García, Muñiz .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La variación morfológica observada entre M. mexicana respecto al individuo de Zumpahuacán (seis caracteres) y el de Malinalco (siete caracteres), sugiere también una diferenciación a nivel específico, ya que la reclasificación a nuevas especies de algunas poblaciones de M. mexicana ha resultado de variaciones morfológicas similares; por ejemplo, la reclasificación a M. perezfarrerae refirió variación en seis caracteres (Vázquez-García, Gómez-Domínguez, et al, 2013), la reclasificación a M. lacandonica consideró cuatro caracteres (Vázquez-García, Pérez-Farrera, et al, 2013), la reclasificación a M. zoquepopolucae contempló siete caracteres (Vázquez-García, De Castro-Arce, et al, 2012) y similar número de diferencias se consideraron en el resto de especies mexicanas de la sección Talauma recientemente descritas (Vázquez-García, Muñiz .…”
Section: Discussionunclassified
“…Aun cuando la caracterización morfológica ha permitido la discriminación de especies en otras magnolias (Vázquez-García, Gómez-Domínguez, et al, 2013;Vázquez-García, Pérez-Farrera, et al, 2013), el empleo de marcadores moleculares ha probado su utilidad en este grupo por las muestras mínimas de tejido requerido y su capacidad discriminatoria entre poblaciones; tal es el caso de los marcadores RAPD (Polimorfismos de ADN Amplificados al Azar, por sus siglas en inglés), que se han mantenido vigentes, a pesar de su relativa baja reproducibilidad, por su simplicidad técnica (Kelleher & Diskin, 2018;Larekeng, Dermawan, Iswoyo, & Mustari, 2019;Sharma, Sharma, & Kumar, 2018;Weising, Nybom, Wolff, & Kahl, 2005), detección de un nivel alto de polimorfismo (Arumugam, Jayapriya, & Sekar, 2019;Casarrubias-Carrillo et al, 2003;Mondragón-Jacobo, 2003) y su utilidad en la identificación genética de individuos (Rentaría Alcántara, 2007). Así, el objetivo del presente estudio fue establecer las relaciones moleculares y morfológicas existentes entre los árboles de Yoloxóchitl, presentes en Malinalco y Zumpahuacán, Estado de México, con individuos de M. mexicana de Zongolica, Veracruz.…”
Section: Introductionunclassified
“…Although political boundaries do not reflect biogeographic units, we have nonetheless used them, given the small size of most Central American countries and the lack of local biogeographic studies to have a general view of the broad patterns of the species of interest. Thus, we have found that the family displays a remarkable pattern of allopatric speciation in the area, with only seven species (12%) shared between two or more countries (Vázquez-García 1990, Vázquez-García et al 2002, 2012a, 2012b, 2012c, 2013a, 2013b, 2013c, 2013d, Jiménez-Ramírez & Cruz 2005, Jiménez-Ramírez et al 2007, Cruz et al 2008.…”
Section: Introductionmentioning
confidence: 94%
“…600 km², but the current threats include the transformation of their habitat to coffee and corn plantations as well as for pasturelands. This species has extremely reduced populations apparently without regeneration (Vázquez-García et al 2013a, 2013c, 2013d. Although population numbers are not known from the entire range, the population is thought to be small with only ten mature trees present at the type locality.…”
Section: Endangered (En): B1ab(iiiiii)mentioning
confidence: 99%
“…Lozano-Contreras's work included 31 Neotropical species in subsect. Talauma, 20 of which he described (Lozano-Contreras 1983, 1994, but the number of species has more than doubled in the last five years (Serna et al 2009;Dillon & Sánchez-Vega 2009, Vázquez-García et al 2012a, 2012b, 2013a, 2013b, 2013c, 2013d, 2014Marcelo-Peña & Arroyo 2013, Arroyo 2014. Additional (ca.…”
Section: Introductionmentioning
confidence: 99%